Empirical Study of Differentiated Learning Using The Moodle Platform on Personalized Informatics Subjects in Vocational High Schools - Kusnendar, Jajang; Darmawan, Deni; Rusman, Rusman; Rachman, Indriyani (Journal of Education Technology, 2025)
Students have diverse learning abilities, however, in its implementation, learning is still found to be based on the teacher's wishes, not based on the students' learning needs. The diversity of students' learning styles is neglected, and teachers have difficulty accommodating it due to limited space and time. Therefore, it is important to implement differentiated learning to improve learning outcomes through personalized learning. This study aims to examine the application of differentiated learning using the Learning Management System (LMS) Moodle, through personalized learning and describe student responses. The method used is descriptive qualitative. Direct interviews with student representatives were conducted to determine responses to differentiated learning. Personalized learning is used by utilizing Moodle features in configuring teaching materials to facilitate student learning preferences which are packaged in three types as a manifestation of content differentiation and configuration in formative and remedial summative tests as a form of process differentiation. The results of the study indicate that: 1) a differentiated learning pattern was found, where each student has a varied learning pattern and preference for the teaching materials provided; 2) process differentiation successfully facilitates students' diverse learning abilities to achieve learning completeness; 3) Students responded positively to differentiated learning based on: typical learning preferences, availability of materials, learning readiness, learning speed, and opportunities to complete learning.